2014
DOI: 10.1159/000358128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exposure to Acute and Chronic High-Altitude Hypoxia on the Activity and Expression of CYP1A2, CYP2D6, CYP2C9, CYP2C19 and NAT2 in Rats

Abstract: We investigated the effect of exposure to acute and chronic high-altitude hypoxia (AHH and CHH) on the activity and expression of CYP1A2, CYP2D6, CYP2C9, CYP2C19 and NAT2 in rats. The rats were divided into plain (400 m), acute middle-altitude hypoxia (2,800 m), chronic middle-altitude hypoxia (2,800 m), AHH (4,300 m) and CHH (4,300 m). After probe drugs had been orally administered to the rats of the 5 groups, the serum or urine concentration of the probe drug and its metabolite was determined by reversed-pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Decreased expression of hepatic cytochrome P450 1A2 (CYP1A2) in a chronic intermittent hypoxia mouse model were down-regulated, while CYP3A6 and P-glycoprotein were up-regulated, Li et al demonstrated that the activity of hepatic CYP family, CYP1A2 rather than CYP2C9 and CYP2C19, were decreased after rat were subjected to highaltitude hypoxia (5). A human study with 12 volunteers exposed to altitude-induced hypoxia found that the activity of CYP2D6 and CYP3A4 was slightly reduced (6).…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Decreased expression of hepatic cytochrome P450 1A2 (CYP1A2) in a chronic intermittent hypoxia mouse model were down-regulated, while CYP3A6 and P-glycoprotein were up-regulated, Li et al demonstrated that the activity of hepatic CYP family, CYP1A2 rather than CYP2C9 and CYP2C19, were decreased after rat were subjected to highaltitude hypoxia (5). A human study with 12 volunteers exposed to altitude-induced hypoxia found that the activity of CYP2D6 and CYP3A4 was slightly reduced (6).…”
Section: Original Articlementioning
confidence: 99%
“…CIH easily triggers systemic inflammation, oxidative stress, endothelial damage, and metabolic abnormalities (7). Numerous data demonstrated the impact of sustained hypoxia on hepatic CYP and drug metabolism (3)(4)(5)32). Patients with chronic sustained hypoxia were advised to adjust the dosage of drugs (6).…”
Section: R O B U S T E V I D E N C E S H O W E D T H a T O Smentioning
confidence: 99%
“…Recently, Rahman and Thomas [27] found that exposure to hypoxia for 2 weeks caused significant decreases in hepatic CY-P1A mRNA and protein levels compared with CYP1A levels in fish in normoxic-condition in vivo studies. Our recent study found that acute and CHH caused significant decreases in the activity, protein and mRNA expression of rat CYP1A2 in vivo, and that CHH upregulated the activity, protein and mRNA expression of rat CYP2D6 [28] .…”
Section: Discussionmentioning
confidence: 86%
“…The liver tissues were immediately frozen in liquid nitrogen. The liver microsomes were prepared using differential centrifugation according to our previous reports . Briefly, liver samples were thawed and weighed, and two volumes of ice‐cold homogenization medium (50 mmol/L Tris‐HCl buffer at pH 7.4 containing 0.25 m sucrose) were then added.…”
Section: Methodsmentioning
confidence: 99%
“…The expression of CES1 and CYP3A1 was determined by ELISA according to our previous reports . Briefly, to establish a bland well without any solution, 50 μL of standard and 40 μL of sample diluted solution were added to standard and sample wells with a biotin‐conjugated antibody specific to CES1 and CYP3A1, respectively.…”
Section: Methodsmentioning
confidence: 99%